A facile and high-yield formation of dipyrrin-boronic acid dyads and triads: a light-harvesting system in the visible region based on the efficient energy transfer1. Issue 9 (7th March 2015) - Yamamura, Masaki; Yazaki, Shinya; Seki, Motofumi; Matsui, Yasunori; Ikeda, Hiroshi; Nabeshima, Tatsuya
<x xml:space="preserve">Abstract</x> Artificial light-harvesting systems, Ar, O-BODIPY dyads and triads conjugated with a light harvester, were synthesized in high yield by the reaction of an N2O2-type dipyrrin with boronic acids.